Star Wars: The Force Awakens - J.J. Abrams (2026)
Star Wars; The Force Awakens is a 2015 American epic space opera film produced co-written and directed by J. J. Abrams. It is the first installment of the Star Wars sequel trilogy following Return of the Jedi (1983) and the seventh episode of the nine-part "Skywalker saga".